Are Putative Periodontal Pathogens Reliable Diagnostic Markers? - Riep, Birgit; Edesi-Neuss, Lilian; Claessen, Friderike; Skarabis, Horst; Ehmke, Benjamin; Flemmig, Thomas F; Bernimoulin, Jean-Pierre; Göbel, Ulf B; Moter, Annette (Journal of Clinical Microbiology, 2009)
Periodontitis is one of the most common chronic inflammatory diseases. A number of putative bacterial pathogens have been associated with the disease and are used as diagnostic markers. In the present study, we compared the prevalence of oral bacterial species in the subgingival biofilm of generalized aggressive periodontitis (GAP) (n = 44) and chronic periodontitis (CP) (n = 46) patients with that of a periodontitis-resistant control group (PR) (n = 21). The control group consisted of subjects at least 65 years of age with only minimal or no periodontitis and no history of periodontal treatment. A total of 555 samples from 111 subjects were included in this study. The samples were analyzed by PCR of 16S rRNA gene fragments and subsequent dot blot hybridization using oligonucleotide probes specific for Aggregatibacter (Actinobacillus) actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, a Treponema denticola-like phylogroup (Treponema phylogroup II), Treponema lecithinolyticum, Campylobacter rectus, Fusobacterium spp., and Fusobacterium nucleatum, as well as Capnocytophaga ochracea. Our data confirm a high prevalence of the putative periodontal pathogens P. gingivalis, P. intermedia, and T. forsythia in the periodontitis groups. However, these species were also frequently detected in the PR group. For most of the species tested, the prevalence was more associated with increased probing depth than with the subject group. T. lecithinolyticum was the only periodontopathogenic species showing significant differences both between GAP and CP patients and between GAP patients and PR subjects. C. ochracea was associated with the PR subjects, regardless of the probing depth. These results indicate that T. lecithinolyticum may be a diagnostic marker for GAP and C. ochracea for periodontal health. They also suggest that current presumptions of the association of specific bacteria with periodontal health and disease require further evaluation.